Outcomes of Left Ventricular Assist Devices as Destination Therapy: A Systematic Review with Meta-Analysis - Emad Ali Al Khoufi (Life)
Background: Heart failure (HF) is a chronic condition that significantly affects morbidity and mortality. For patients with end-stage HF who are not candidates for heart transplantation, left ventricular assist devices (LVADs) provide mechanical circulatory support as a long-term solution, known as destination therapy (DT). Objective: This meta-analysis aims to synthesize evidence on the survival rates, complications, and quality-of-life improvements associated with LVADs used as destination therapy in patients with end-stage HF. Methods: A systematic search of databases, including PubMed, Embase, Cochrane Library, Web of Science, and Scopus, was conducted to identify relevant studies. Studies were selected based on predefined inclusion and exclusion criteria. Data from 12 studies were extracted and analyzed using a random-effects model. Survival rates, complications (e.g., infection and bleeding), and quality-of-life measures were the primary outcomes evaluated. Results: The analysis showed significant improvements in survival, with a pooled effect size of 0.848 (95% CI: 0.306–1.390, p = 0.002). Complication rates varied, with infections and bleeding being the most common adverse events. Quality of life also improved significantly post-LVAD implantation, with a standardized mean difference of 0.78 (95% CI: 0.65–0.91). Conclusions: LVADs as destination therapy provide a viable option for improving the survival and quality of life of end-stage HF patients, despite the associated risks of complications. Further research is needed to refine patient selection and management strategies to optimize outcomes.